Analisis Meningkatkan Kemampuan Digital Guru Melalui Metode Knowshare pada Masa Pandemic Covid -19 di Komed Depok - Nurkaidah Nurkaidah; Dwi Kartika Susantia (Tarbiatuna: Journal of Islamic Education Studies, 2023)
The research aims to (1) describe the increase in the digital skills of Komed Depok teachers using the Knowshare method during the Covid-19 Pandemic, (2) Analyze the effect of increasing the digital abilities of Komed Depok teachers with the knowshare method during the Covid-19 pandemic. Using quantitative. The sample is 47 teachers from the c community in Depok. Respondents from various levels of kindergarten, elementary and high school. public and private schools. 80% private and 20% state. Female respondents 44 (93.6%) male respondents 3 (6.4 %). The results of the analysis of teachers' digital abilities before and after participating in KOMED: A. 21 people, 47.18% of respondents have increased digital skills. Comparison of teachers' digital abilities and pedagogical and professional competencies is increasing. B. Teachers whose ability remains at 46.9% as before, there is no increase and the intensity of following Shareknow komed is also high at 93.18%. C. komed participants with digital skills decreased by 6.1% because the intensity of participating in komed knowshare was low by 62.50%. Thus, it can be concluded that there is a positive and significant effect between increasing the digital skills of Komed Depok teachers and the knowshare method during the Covid-19 pandemic. Research on the analysis of increasing the digital skills of Komed Depok teachers using the knowshare method during the Covid-19 pandemic can reveal new information regarding the factors for increasing the digital skills of Komed Depok teachers using the knowshare method during the Covid-19 pandemic. The method used is purposive random sampling, the use of questionnaires and descriptive analysis. Keywords: 1, Teacher digitization ability 2; KnowShare Method 3; Covid-19 pandemic Analisis Meningkatkan Kemampuan Digital Guru Melalui Metode Knowshare Pada Masa Pandemic Covid -19 Di Komed Depok Nurkaidah1, Dwi Kartika Susantia,2 1 Program Studi PPKn STKIP Arrahmaniyah Depok 2 Pendidikan Biologi STKIP Arrahmaniyah Depok nurkaidah2203@gmail.com, kartika.stkiparrahmaniyah@gmail.com ABSTRACT The research aims to (1) describe the increase in the digital skills of Komed Depok teachers using the Knowshare method during the Covid-19 Pandemic, (2) Analyze the effect of increasing the digital abilities of Komed Depok teachers with the knowshare method during the Covid-19 pandemic. Using quantitative. The sample is 47 teachers from the c community in Depok. Respondents from various levels of kindergarten, elementary and high school. public and private schools. 80% private and 20% state. Female respondents 44 (93.6%) male respondents 3 (6.4 %). The results of the analysis of teachers' digital abilities before and after participating in KOMED: A. 21 people, 47.18% of respondents have increased digital skills. Comparison of teachers' digital abilities and pedagogical and professional competencies is increasing. B. Teachers whose ability remains at 46.9% as before, there is no increase and the intensity of following Shareknow komed is also high at 93.18%. C. komed participants with digital skills decreased by 6.1% because the intensity of participating in komed knowshare was low by 62.50%. Thus, it can be concluded that there is a positive and significant effect between increasing the digital skills of Komed Depok teachers and the knowshare method during the Covid-19 pandemic. Research on the analysis of increasing the digital skills of Komed Depok teachers using the knowshare method during the Covid-19 pandemic can reveal new information regarding the factors for increasing the digital skills of Komed Depok teachers using the knowshare method during the Covid-19 pandemic. The method used is purposive random sampling, the use of questionnaires and descriptive analysis. Keywords: Teacher digitization ability, KnowShare Method , Covid-19 pandemic